Design and Evaluation of a Novel Multiplex Real-Time PCR Melting Curve Assay for the Simultaneous Detection of Nine Sexually Transmitted Disease Pathogens in Genitourinary Secretions - Hu, Xiao-Mei; Xu, Jiang-Xia; Jiang, Li-Xia; Deng, Lian-Rui; Gu, Zhen-Mei; Xie, Xiao-Ying; Ji, Hui-Cai; Wang, Wei-Hua; Li, Li-Ming; Tian, Cheng-Nan; Song, Fang-Li; Huang, Shao; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Background: Sexually transmitted diseases (STD) are a major cause of infertility, long-term disability, ectopic pregnancy, and premature birth. Therefore, the development of fast and low-cost laboratory STD diagnostic screening methods will contribute to reducing STD-induced reproductive tract damage and improve women's health worldwide. In this study, we evaluated a novel multiplex real-time PCR melting curve assay method for the simultaneous detection of 9 STD pathogens, including Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, Trichomonas vaginalis, Mycoplasma hominis, Ureaplasma urealyticum, Ureaplasma parvum, and herpes simplex virus. Methods: The analytical performance of the method, including its limit of detection (LOD), specificity, repeatability, and effect on different DNA extraction kits were evaluated. Additionally, we obtained 1328 clinical specimens from 3 hospitals to detect the 9 STD pathogens using multiplex real-time PCR melting curve and Sanger sequencing, to evaluate the sensitivity, specificity, and consistency of the assay method. Results: The results showed that the analytical sensitivity of the novel multiplex real-time PCR melting curve assay is very excellent, with LOD of DNA corresponding to less than 200 copies/μl for the DNA of the 9 STDs and 1.00×104 color change unit /ml for those of UU and UP. Additionally, this assay demonstrated excellent analytical specificity, excellent repeatability, and its results had no effect of different DNA extraction kits. The performance, in terms of sensitivity (91.06-100%) and specificity (99.14-100%), was remarkable, since the consistency between it and Sanger sequencing was more than 0.85 in the clinic. Conclusion: The novel multiplex real-time PCR melting curve assay method has high sensitivity and specificity, relatively low cost, and simple to use for the simultaneous detection of 9 STD pathogens in genitourinary secretions